Sebaran Hasil Belajar Pendidikan Agama Islam Sekolah Menengah Pertama: Ditinjau dari Sistem Zonasi - Sakurina, Imro Atun; Khuriyah, Khuriyah (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2022)
There is a disparity in PAI learning outcomes between superior schools and ordinary schools in junior high schools in Karanganyar District. The government overcomes this problem by implementing a zoning system. This study aims to determine the difference in the distribution of PAI learning outcomes between students of SMPN 1 Karanganyar and students of SMPN 5 Karanganyar. The research method used is ex-post-facto. The place of this research was carried out at SMP Negeri 1 Karanganyar representing previously superior schools and at SMP Negeri 5 Karanganyar representing previously ordinary schools. The population in this study amounted to 1057. The research sample obtained 290 students. The sampling technique used is Stratified Random Sampling and Purposive Sampling. Data collection using the document method. Normality test using chi-square test. The homogeneity of variance test used the Bartlett test and the hypothesis test used the X2 test formula for two independent samples. The results showed that it was evident from the results of X2count dan X2table, 9.147 > 0.00016, then Ha was accepted and Ho was rejected, so it can be concluded that there is a difference in the distribution of PAI learning outcomes between superior junior high school students and ordinary junior high school students. or it can be said that the interaction effect of school quality and the Acceptance of New Students system on PAI learning outcomes.